Giftedness in Arabic environments: Concepts, implicit theories, and the contributed factors in the enrichment programs - Abdullah M. Aljughaiman; Alaa Eldin A. Ayoub (Cogent Education, 2017)
The study aimed at identifying specific giftedness patterns that teachers discriminate against, and for, when nominating gifted students and focused on the identification of implicit theories adopted by teachers on the topics of intelligence, giftedness, and creativity in light of their specialization and experience. The study examined the differences between the effect of summer enrichment programs and school enrichment programs on students’ performance. Profiles for types of gifted students were created, and implicit theory scales and performance assessment scales were implemented. The results showed that regardless of teachers’ specialization and experience, they tended to increasingly nominate students who are intellectually, creatively, and academically gifted. On the other hand, they are strongly biased against students who were gifted in visual arts, psychomotor, and leadership fields, as well as gifted underachievers. Gifted students’ teachers tended to incremental theories in all fields, compared to classroom teachers who tended to entity theories. The results revealed that differences exist in the effectiveness of summer enrichment programs and school enrichment programs, as gifted students’ performance was favorable in summer enrichment programs. Results showed that trainers’ experience with giftedness programs was a factor on students’ performance, and was dependent on the type of program, age of students, number of students, and trainers’ qualifications.